2010
DOI: 10.1889/jsid18.11.931
|View full text |Cite
|
Sign up to set email alerts
|

Measuring visual fatigue and visual discomfort associated with 3‐D displays

Abstract: Abstract— This research identifies methods for signs of visual complaints associated with stereoscopic displays. Two potential causes for contradictory results concerning these signs in previous research are hypothesized: (1) not all clinical tests are equally appropriate and (2) there is a natural variation in susceptibility amongst people with normal vision. An optometric screening differentiated participants with moderate binocular status (MBS) from those with good binocular status (GBS). In a 2 × 2 within‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…Previous studies have shown that people with binocular dysfunction may be more susceptible to having symptoms associated with viewing 3D contents. 22,23 Mainos 24 reported that accommodative and vergence dysfunctions can lead to the manifestation of symptoms in users when watching 3D contents and that the improvement in binocular vision by visual therapy may reduce its manifestation. Kim et al, 25 demonstrated that the use of binocular vision corrective spectacles can reduce the manifestation of symptoms when viewing 3D contents.…”
Section: Accommodative Response To 2d and 3d Stimulimentioning
confidence: 99%
“…Previous studies have shown that people with binocular dysfunction may be more susceptible to having symptoms associated with viewing 3D contents. 22,23 Mainos 24 reported that accommodative and vergence dysfunctions can lead to the manifestation of symptoms in users when watching 3D contents and that the improvement in binocular vision by visual therapy may reduce its manifestation. Kim et al, 25 demonstrated that the use of binocular vision corrective spectacles can reduce the manifestation of symptoms when viewing 3D contents.…”
Section: Accommodative Response To 2d and 3d Stimulimentioning
confidence: 99%
“…23,24 It is simple to identify observers by implementing the subjective evaluation that are particularly sensitive to visual fatigue. 25 Several methods for subjective evaluation of visual discomfort have been tested. 26 The questionnaires consist of questions with a self-rated score concerning subjective symptoms of fatigue.…”
Section: Human-factors Evaluationmentioning
confidence: 99%
“…28 Many viewers felt dizzy, even close to death, after watching 3-D movies. 22,25,28 Therefore, this study included the psychophysical and physiological reaction measurement while watching stereo images and films. A flicker fusion apparatus and an autonomic nervous system (ANS) watch were used in this research.…”
Section: Human-factors Evaluationmentioning
confidence: 99%
“…However, notwithstanding this worldwide success, the potential drawbacks of such a new technology cannot be ignored. One of the major problems encountered by viewers is visual discomfort [2][3][4][5][6], which can be framed it in the wider concept of asthenopia, or "weak eye" [8]. Asthenopia is a macrocategory encompassing several symptoms that can be assessed through subjective and objective methods [2] (Fig.…”
Section: Introductionmentioning
confidence: 99%